Sequential bilingualism and the teaching of language skills to early primary school pupils in Nigeria - Adgebide, Wale (Glottodidactica, 2000)
This paper argues that the poor mastery of language skills in Nigeria's educational system can be attributed partly to the poor methods of teaching language skills in the system, especially in early primary education. Given the fact that the bilingual concept is entrenched in the 1977 (revised 1981) Nigeria National Policy on Education, the approach of ‘simultaneous’ bilingualism has been utilised in teaching mother tongue and English language skills - listening, speaking, reading and writing - in the primary schools for a long time now. The use of this approach is noticeable, especially, in classroom presentation and text book development. However, it is apparent that the approach has not been effective and, thus, has not enhanced the inculcation of permanent literacy which is a major objective of the educational policy. Using illustrations from some common Yoruba (mother tongue) and English course books for pupils in early primary education in Nigeria, the paper observes some of the limitations of simultaneously presenting language skills to children in early primary education, and suggests that the sequential presentation of skills be done to promote efficient bilingual education in the school system. The paper suggests that teachers and writers of course books of Yoruba and English should present language skills in a way in which some skills learnt earlier will facilitate the learning of later ones.